2006
DOI: 10.1007/s00259-006-0154-y
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of 4-borono-2-[18F]fluoro-L-phenylalanine in sporadic and neurofibromatosis 2-related schwannoma and meningioma studied with PET

Abstract: [(18)F]FBPA PET offers a viable means to evaluate BPA uptake in meningiomas and schwannomas in NF2. Based on our results on tumour uptake of [(18)F]FBPA, some of these benign neoplasms may be amenable to BNCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…For these purposes, numerous authors have used 18 F-BPA-PET prior to employing BPA-based BNCT, and reported its usefulness (11)(12)(13)(14). However, the possibility of detecting the spatial localization of the tumor as well as delineation of normal anatomical structures has yet to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…For these purposes, numerous authors have used 18 F-BPA-PET prior to employing BPA-based BNCT, and reported its usefulness (11)(12)(13)(14). However, the possibility of detecting the spatial localization of the tumor as well as delineation of normal anatomical structures has yet to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…PET was carried out with either a GE Advance or a GE Discovery STE scanner (GE Medical Systems, Milwaukee, WI) operated in three-dimensional (3D) mode by use of intravenously administered 18 F-fluoro-L-BPA at activity of 160 to 240 MB as the tracer (17). Tumor-to-normal tissue ratios were measured from static emission scans obtained 20 to 40 minutes after 18 F-fluoro-L-BPA injection.…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…Following a similar approach, recent applications have demonstrated the potential of PET imaging for the assessment of BPA accumulation in lesions different from high grade glioma. 18 F-BPA has been used in recurrent cancer in the oral cavity and cervical lymph node metastasis (2007) [117], low grade brain tumors, such as schwannoma and meningioma (2006) [118], head and neck malignancies (2005) [30] and metastatic malignant melanoma (2003) [119]. These early clinical findings with 18 F-BPA/PET led to study the transport and the net influx and accumulation of BPA, and to show the capability of PET to screen the different types and different grades of tumor lesions as candidates for BNCT [120].…”
Section: Positron Emission Tomography (Pet)mentioning
confidence: 99%